The Problem of Historical Fact - Valevičius, Vytautas (Problemos, 1987)
The concept and the structure of scientific fact and its applicability in the historical knowledge is discussed in the article. First, the general understanding of empirical data and scientific fact is presented, and then the specific character of the science of history is revealed. As the result, the peculiarities of the formulation of historical fact and its place in this particular field of scientific knowledge are cleared up.